Ambivalence regarding tuberculosis control actions in primary health care - Reinaldo Antonio Silva-Sobrinho; Adriana Zilly; Aline Aparecida Monroe; Érika Simone Galvão Pinto; Rosane Meire Munhak da Silva; Tereza Cristina Scatena Villa (Rev Rene)
his study aimed to evaluate health professionals’ perception regarding the organization and functioning of the Tuberculosis Control Program in Foz do Iguaçu, PR, Brazil. It is a qualitative study, in which the thematic axis was the structure and the centralization/decentralization of the control of tuberculosis. It was undertaken through open interviews, held in May 2009. Based on these, the empirical material was organized in the light of content analysis. The results revealed weakness in relation to the dimension of the physical structure and the human resources. Questions arose indicating Directly Observed Treatment as a paternalistic action. It was evidenced that there is a need for managers to take a position regarding the decentralization of tuberculosis control to Primary Health Care. However, the Central Thematic Unit revealed ambivalence relating to this theme. It is concluded that the Program, generally speaking, functions in line with the Ministry of Health’s recommendations.